DNA methylation mechanisms in the maturing and ageing oocyte - Carla Caniçais; Sara Vasconcelos; Fátima Santos; Sofia Dória; C. Joana Marques (Epigenetics & Chromatin)
Abstract Oocyte maturation involves both nuclear and cytoplasmic processes that are critical for the acquisition of oocyte competence. Granulosa cells, surrounding the oocyte, play a pivotal role in the maturation process, with mechanisms such as cAMP signaling significantly influencing oocyte development. Epigenetic mechanisms – including DNA methylation and its oxidative derivatives, histone post-translational modifications and chromatin remodeling – interfere with the accessibility of transcription factors to regulatory regions of the genome, such as promoter regions of genes, hence generally regulating gene expression profiles; however, in oocytes, transcription is largely independent of DNA methylation patterns. Here we highlight epigenetic reprogramming events occurring during oocyte development and ageing, focusing on the establishment of gamete-specific epigenetic marks, including DNA modifications at imprinted regions, and age-related epigenetic changes. We focus on the mechanisms of DNA methylation and demethylation during mouse and human oocyte maturation, alongside an exploration of how ageing impacts the oocyte epigenome and its implications for reproductive success. By providing a comprehensive analysis of the role of epigenetics in oocyte development and maturation, this review addresses the importance of comprehending these processes to enhance in vitro fertilization treatments and improve reproductive outcomes.